(3cTa GdefGgL hGdJaGJjM aj TQM CMGOjK GdeUGHjMs - (3CHhYHO Gddg eMeO TQa GdOjf EHQGgje GdSdej GdefGhj GdTGaYjs; (3GdHZhj , GdMSjf Hf eSYhO Hf eMeO GdaQGA, eMjj GdSfI CHh eMeO,J (B510 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi CLeY GdeUfaGJ GdeNJUQGJ aj GdCNHGQ GdfHhjI hCMSf GdeDdaGJ GdLGeYGJ ddBKGQ GdeMeOjI cJGH GdeUGHjM LeY GdYdGeI GdEeGe GdHZhj s
(3BNQgG (B:s
(3haj QhGjI Cfg SCd GdfHj Udi Gddg Ydjg hSde Yf CjJGe hQKhG NeQkG bGd CgQbgG bGd CadG CLYdgG NdkG bGd G BNQ GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B61s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1701s
Keywords: (3GdMOjK h GdeUWdMs